Are Avoidance Goals the Right Prescription For a Pandemic? A COVID-19 Case Study - Geoffrey V. Henderson; Andrew J. Elliot (Ital Publication, 2021)
Background: Motivation scientists study goals, self-regulatory tools that are used to help people approach or avoid objects of desire or disdain. Purpose: Using these tools, motivation science can offer insights to guide behaviour and help individuals maintain optimal health and well-being during pandemics, including COVID-19. Results: Avoidance goals help guide behaviour away from negative objects like COVID-19, and are necessary in situations where survival is at stake. Formulating the goal of avoiding COVID-19 is therefore recommended during the pandemic. However, avoidance goals have inherent limitations, in that they tax one's energy and well-being. To minimize these costs, the pursuit of approach sub-goals may be recommended, such as increasing social connection online or exercising outdoors (particularly prior to widespread vaccination). Conclusion: Adhering to the goal of avoiding COVID-19 prevents infection and saves lives when safe and effective vaccines and treatments are lacking. But avoidance goals have known costs that must be acknowledged and addressed. One solution is to pair avoidance goals with approach sub-goals to bolster mental and physical health while adhering to the ultimate goal of avoiding COVID-19, viral variants, and future contagions.   Doi: 10.28991/SciMedJ-2021-0304-7 Full Text: PDF